Situational awareness in the management of pediatric abdominal impalement - Caroline M. Godfrey; Harold N. Lovvorn, III; Amber Greeno; Eunice Huang (Elsevier, 2022)
Non-firearm abdominal impalement is a rare presentation of pediatric trauma and presents unique challenges. Here, we present the case of a 13-year-old girl who sustained transabdominal impalement of a tree branch from a sledding accident in which she was being towed behind an ATV. Complicating her care was a concurrent, city-wide state of emergency in which internet and cellular communications were impaired after the bombing of a communication building. To characterize trajectory, computer tomographic (CT) scan imaging showed the branch traversed the right retroperitoneum, obstructing the ureter and inferior vena cava, passed adjacent to the inferior wall of the 4th portion of the duodenum, perforated the stomach, and exited the peritoneum through the left abdominal wall musculature. Laparotomy identified lacerations to the anterior and posterior gastric walls, a duodenal laceration, and significant debris throughout the abdomen. Three visceral defects were closed primarily. A contrast study on POD5 confirmed integrity of the repairs. She recovered well and was discharged on POD13. This case highlights the importance of evaluating patient-specific mechanism of injury ("look at"), assessing patients in real time when provider communications are limited due to any disaster ("look up"), and sharing with the community critical public health lessons ("look around").